Digital Transformations in Mongolia: Challenges and Opportunities - A. Davaasuren (Informaciâ i Innovacii)
The rapid development of information technology in the world has changed the traditional system of the world economy. The Internet space has become the main infrastructure for the development of finance, economy and trade, which contributes to the rapid socio-economic development of the world’s countries. The article considers the current trends in the development of digital transformation in the world, as well as the state of digital transformation in Mongolia. The challenges, opportunities, advantages, and risks of digital transformation in the country are highlighted. Today, there are no industries in the economy of Mongolia that do not carry out their activities through the tools of digital economy and do not use digital or information technologies. The information and telecommunications industry is becoming one of the main sectors of the country’s economy and has become a driving force for the development of all other sectors of the economy. Cybersecurity issues are of particular importance.